Sensing task handover for indoor clustered wireless sensor network - Pu, Chuan Chin * (2011)
This paper presents the proposal of implementing sensing task handover initiation control for wireless sensor network deployed in indoor environment. The structure of the wireless sensor network is based on indoor clustering so that sensor nodes are grouped in different clusters according to room partitions. For such a network, a simple and efficient multi-node handover initiation control method is proposed for the decision of handover initiation by comparing the combined received signal strengths and the number of effective nodes between two neighbouring clusters. Experiments were conducted to test the possibility and evaluate the performance of the proposed method. The results show that sensing task handover is possible to happen at accurate time while crossing boundary between two clusters by applying the proposed method.